2015
DOI: 10.1017/s0031182015000530
|View full text |Cite
|
Sign up to set email alerts
|

Symbiosis in an overlooked microcosm: a systematic review of the bacterial flora of mites

Abstract: A dataset of bacterial diversity found in mites was compiled from 193 publications (from 1964 to January 2015). A total of 143 mite species belonging to the 3 orders (Mesostigmata, Sarcoptiformes and Trombidiformes) were recorded and found to be associated with approximately 150 bacteria species (in 85 genera, 51 families, 25 orders and 7 phyla). From the literature, the intracellular symbiont Cardinium, the scrub typhus agent Orientia, and Wolbachia (the most prevalent symbiont of arthropods) were the dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 109 publications
(213 reference statements)
3
28
0
1
Order By: Relevance
“…Overall, many other species of sarcoptiform mites, including many free‐living Astigmata, are functionally defined as fungivore–microbivore–detritivores (e.g., Pyroglyphidae and most oribatid mites, Walter & Proctor 2013a,b), and our results also support this classification for feather mites. In fact, our results are in large agreement with previous studies on microbes found in other mite species (Chaisiri, McGarry, Morand, & Makepeace, ; Hubert et al., ), where strong evidence has been found for the utilization of bacteria as a food source in free‐living astigmatan species (Erban & Hubert, , ; Hubert, Nesvorna, Kopecký, Ságová‐Marečková, & Poltronieri, ; Hubert et al., ). In these studies, microbiomes composed of highly diverse taxa in low abundance have been interpreted as evidence for microbivory.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, many other species of sarcoptiform mites, including many free‐living Astigmata, are functionally defined as fungivore–microbivore–detritivores (e.g., Pyroglyphidae and most oribatid mites, Walter & Proctor 2013a,b), and our results also support this classification for feather mites. In fact, our results are in large agreement with previous studies on microbes found in other mite species (Chaisiri, McGarry, Morand, & Makepeace, ; Hubert et al., ), where strong evidence has been found for the utilization of bacteria as a food source in free‐living astigmatan species (Erban & Hubert, , ; Hubert, Nesvorna, Kopecký, Ságová‐Marečková, & Poltronieri, ; Hubert et al., ). In these studies, microbiomes composed of highly diverse taxa in low abundance have been interpreted as evidence for microbivory.…”
Section: Discussionsupporting
confidence: 92%
“…Several bacteria have been shown to associate with mites and ticks [17, 49, 50]; however, bacteria associated with honey bee mites have not yet been fully investigated [11]. We thus attempted to identify any bacteria associated with T. mercedesae by filtering the bacteria-derived DNA contigs during the mite genome assembly.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, many mite species were reported to harbor this symbiont (Duron et al 2008;Ros et al 2012;Kopecky et al 2013;Famah Sourassou et al 2014;Weinert et al 2015;Chaisiri et al 2015). There are several studies reporting Cardinium-induced reproductive alterations in mites (Weeks & Stouthamer 2004;Groot & Breeuwer 2006;Gotoh et al 2007;Ros & Breeuwer 2009;Liu et al 2010;Xie et al 2010;Wu & Hoy 2012;Zhu et al 2012b;Zhao et al 2013a;Zhao et al 2013b;Famah Sourassou et al 2014), and Cardinium seem to be essential for oviposition in the Ghana population of Neoseiulus paepalivorus (Famah Sourassou et al 2014).…”
Section: Reviewmentioning
confidence: 99%
“…For instance, Chaisiri et al (2015) have revealed that mite species were associated with 85 bacterial genera (approximately 150 identified species) belonging to 7 phyla and 25 orders. Among these bacteria, Cardinium, Wolbachia and Orientia are the most prevalent bacteria.…”
Section: Multiple Infections Of Cardinium and Other Endosymbionts In mentioning
confidence: 99%